miRNA and mRNA Profiles in Ventral Tegmental Area From Juvenile Mice With Companion Communication of Improving CUMS-Induced Depression-Like Behaviors - Song, Zhenhua; Wang, Jin-hui (Frontiers in Psychiatry, 2021)
Under chronic stress, the appearance of depression-like behaviors may be related to the decline of the brain's reward circuit function which caused by long-term lack of reward. However, the effect of reward treatment on depressive-like behaviors induced by chronic stress and its molecular mechanism in the brain remain poorly understood. Here, accompanying with companion was used to imitate a reward to study the effect of reward on depression-like behaviors induced by chronic unpredicted mild stress (CUMS), and high-throughput sequencing was used to analyze the miRNA and mRNA profiles in ventral tegmental area (VTA) harvested from depression-like and resilient behaviors mice. We observed that CUMS-induced depression-like behaviors were ameliorated by accompanying with companion in mice, and 202 differentially expressed genes (DEGs) were found to be associated with depression-like behaviors, 27 DEGs associated with resilience, 159 DEGs associated with accompanying with companion. Importantly, we also obtained 228 differentially expressed miRNAs that associated with accompanying with companion. Furthermore, the miRNA-mRNA network associated with companion was established in ventral tegmental area, based on the miRNA and mRNA profiles. Altogether, our results uncover a new way to ameliorate depression-like behavior, as well as many potential drug targets to prevent or treat depression.